Adsorption behavior of in-house developed CO2-philic anionic surfactants - SeyedehHosna Talebian; Muhammad Sagir (Scientific Reports)
Abstract Incorporating CO2-philic functionalities into surfactant structure is proposed to address the drawbacks of conventional foaming agents such as premature rupture of lamellae in contact with oil, surfactant loss due to adsorption on rock or partitioning between oil and water, and salinity and temperature tolerance issues. Increased activity at the gas/water interface and less surfactant adsorption to the rock due to the presence of CO2-philic chains results in higher foam durability in the presence of oil. In the present paper, a comprehensive study on the adsorption of anionic CO2-philic surfactants onto sandstone rock surface is performed to understand adsorption mechanisms through the addition of CO2-philic tail groups in surfactant structure by observing the changes in concentration, static adsorption, and point of zero charge measurements. The static adsorption tests, Fourier Transform Infrared, and the X-ray Photoelectron Spectroscopy techniques were employed to investigate the interaction of surfactants with crushed Berea sandstone core sample at 90 °C. The static adsorption values of the S (single-tail), D (double-tail), and T (triple-tail) anionic surfactants were reported to be 0.53, 0.40, and 0.6 mg /g, respectively. The effect of alkali on the adsorption process of surfactants was also investigated and the adsorption of synthesized surfactants was found significantly low in alkaline conditions. A variety of analyses, including model fitting along with kinetics and thermodynamics studies at 30, 40, and 50 °C were performed to predict the adsorption behavior. The adsorption isotherm was found to best fit in Langmuir model. The process showed the best fit in the pseudo-second-order reaction kinetics model. The spontaneity of the adsorption process was verified by thermodynamic feasibility studies of the process.